2018
DOI: 10.1021/acs.est.8b02212
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Microplastics on the Soil Biophysical Environment

Abstract: Soils are essential components of terrestrial ecosystems that experience strong pollution pressure. Microplastic contamination of soils is being increasingly documented, with potential consequences for soil biodiversity and function. Notwithstanding, data on effects of such contaminants on fundamental properties potentially impacting soil biota are lacking. The present study explores the potential of microplastics to disturb vital relationships between soil and water, as well as its consequences for soil struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
569
6
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,248 publications
(600 citation statements)
references
References 39 publications
19
569
6
6
Order By: Relevance
“…Interestingly, the effect of the EPDM granules on biomass production of P. lanceolata was non‐monotonically dependent on the granules’ concentration. Recently, Souza Machado, Lau, et al () found also non‐monotonic effects of microplastics on several proxies of the soil biophysical environment. In that study, however, effects of low concentrations were stronger than effects of higher concentrations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, the effect of the EPDM granules on biomass production of P. lanceolata was non‐monotonically dependent on the granules’ concentration. Recently, Souza Machado, Lau, et al () found also non‐monotonic effects of microplastics on several proxies of the soil biophysical environment. In that study, however, effects of low concentrations were stronger than effects of higher concentrations.…”
Section: Discussionmentioning
confidence: 95%
“…Consequently, research on plastic pollution in aquatic ecosystems has increased in recent years (Eerkes-Medrano, Thompson, & Aldridge, 2015;Jambeck et al, 2015). Much less attention has been paid to the potential effects of plastic pollution in terrestrial environments (Rillig, 2012;Rochman, 2018;Souza Machado, Lau, et al, 2018;Windsor et al, 2019). This is surprising, because the release of plastic in terrestrial ecosystems is likely to be higher than in the oceans.…”
Section: Introductionmentioning
confidence: 99%
“…In soil, fertilizers made from recycled waste, as well as street runoff, including abrasions from tires and breaks may be a source of MP [37]. The presence of MP could change soil structure and behavior [14,15]; nevertheless, the main effect seems to be the chemicals leaching out of the plastic material.…”
Section: Germination Rate Index Calculationmentioning
confidence: 99%
“…Terrestrial ecosystems might face MPs pollution earlier than the aquatic ecosystems, and it is currently unknown what impacts MPs might have on the exposed organisms in soil or other substrate systems. Changes in soil structure and terrestrial geochemistry (water holding capacity, hydraulic conductivity, soil aggregation and microbial activity) already have been shown [14,15] which could affect the soil community [16].…”
Section: Introductionmentioning
confidence: 99%
“…Microplastics can also influence soil physical characteristics including bulk density and water dynamics (Liu et al, ; Souza Machado et al, ; de Souza Machado, Lau, et al, ), interestingly decreasing overall soil bulk density but increasing density of the rhizosphere (de Souza Machado et al, ). This ‘ecosystem engineering’ may be partly responsible for microplastics’ effects on soil microbial communities (Qian et al, ; de Souza Machado, Lau, et al, ) and plants (Jiang et al, ; Qi et al, ; Rillig, Lehmann, Machado, & Yang, ; de Souza Machado et al, ). Microplastics also affect these organisms directly.…”
Section: Introductionmentioning
confidence: 99%